2001
DOI: 10.2337/diacare.24.12.2102
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Compliance Is Reduced in the Early Stages of Type 1 Diabetes

Abstract: OBJECTIVE -To determine whether arterial compliance of patients with type 1 diabetes is reduced before the development of clinically apparent diabetes complications.RESEARCH DESIGN AND METHODS -Pulse-wave analysis was used to compare vascular compliance between patients with type 1 diabetes and nondiabetic control subjects. Analysis of covariance was used to determine differences between the two groups with adjustment for age if needed.RESULTS -A total of 59 patients with type 1 diabetes were studied; age rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 28 publications
3
37
0
1
Order By: Relevance
“…However, previous observations showed no (19) or only marginally increased pulse pressure values (Ͻ5 mmHg) in young (25-30 years of age) type 1 diabetic patients (2,3,20). A recent study reported an 11-mmHg higher brachial pulse pressure and an 8-mmHg higher carotid pulse pressure in patients with 15.3 years of type 1 diabetes duration compared with control subjects (21).…”
Section: Resultsmentioning
confidence: 93%
“…However, previous observations showed no (19) or only marginally increased pulse pressure values (Ͻ5 mmHg) in young (25-30 years of age) type 1 diabetic patients (2,3,20). A recent study reported an 11-mmHg higher brachial pulse pressure and an 8-mmHg higher carotid pulse pressure in patients with 15.3 years of type 1 diabetes duration compared with control subjects (21).…”
Section: Resultsmentioning
confidence: 93%
“…Arterial stiffness is determined by both the material properties of the vessel wall (130,142) and the vasoreactivity governed by endothelial function (137,138,143,144). Certain therapeutic agents have shown promise in decreasing arterial stiffness (145,146).…”
Section: Role Of Ages In Promotingmentioning
confidence: 99%
“…In subjects with T1DM, the age-related increase in PP levels can be diagnosed up to 20 years before, even in subjects without nephropathy (9), and it is also associated with CVD (10). In addition, in young subjects with T1DM, an increase in arterial stiffness has also been described (11,12), suggesting a pathogenic role in the early increase of PP in T1DM.…”
Section: Introductionmentioning
confidence: 95%